Determination of Fitness Center Design Criteria with the Approach of Natural Shape and Forms in Surabaya - Pande Putu Dwi Novigga Artha; Bambang Soemardino; Fransiscus Xaverius Teddy Badai Samodra (Institut Teknologi Sepuluh Nopember, 2020)
Surabaya City has the highest activity and density in East Java. This situation affects physical and psychological health. Studies are stating that not exercising regularly is more dangerous than smoking. Therefore, public awareness of the importance of exercising must be increased for the health and national development. In stimulating people to be interested in visiting sports facilities is to apply the biophilic design approach. Restoring the essence of human relations with the nature can be a solution to increase enthusiasm in activities, especially sports in the city of Surabaya, that needs more natural elements. In biophilic theory, several elements can be used as design approaches, one of which is natural shapes and forms. According to Kellert's theory, the natural shapes and forms approach can be applied in 11 elements but these elements are global. By applying the theory of environmental perception, specific natural elements will be obtained with the interests of the people in Surabaya. The analysis results of the design with force-based framework method are specific design criteria for the design of the fitness center with natural shapes and forms approach. This can increase the interest in training and restore the physical and psychological health of its users.